IMMERSIVE LANGUAGE LEARNING THROUGH VIRTUAL REALITY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Virtual Reality (VR) has emerged as a transformative technology in language education, offering immersive and interactive environments for learners. This study explores the effectiveness of VR in enhancing English language learning, particularly in developing speaking skills, vocabulary acquisition, and learner engagement. By simulating real-life communication contexts, VR provides authentic language exposure and reduces anxiety associated with traditional classroom settings. The findings indicate that VR-based learning significantly improves communicative competence, motivation, and retention. The study highlights the pedagogical potential of VR as a key component of future language education.